A biocompatible hydrogel with improved stiffness and hydrophilicity for modular tissue engineering assembly. Issue 14 (14th April 2015) - Wei, Dan; Xiao, Wenqian; Sun, Jing; Zhong, Meiling; Guo, Likun; Fan, Hongsong; Zhang, Xingdong
<x xml:space="preserve">Abstract</x> Inflexible hydrophilic AlgMA was introduced into a bioactive GelMA hydrogel to enhance stiffness and hydrophilicity, thus improving surface tension driven assembly of modular constructs with spatial organized cell distribution and biofunctions.